Creation of IT if the dynamics of TS based system integration of the family of models - Кравчук, Дмитро Олександрович; Лисицький, Василій Лаврентийович (Eastern-European Journal of Enterprise Technologies, 2012)
Features of scientifically well-founded information technology creation of the long-term forecast formation of national economy development taking into account world tendencies and usage of existing models of territorial systems dynamics are considered